Capacitive deionization electrodes and capacitive deionization devices
Patent Information
- Application Number
- CN202411276718.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-09-11
AI Technical Summary
但当前寿命较短的问题限制了其在净水中的进一步应用
[0003]本发明旨在至少在一定程度上解决现有技术中的技术问题之一。为此,本发明的一个目的在于提出一种电容去离子电极和电容去离子器件。
Smart Images

Figure CN119059615B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of water treatment technology, and in particular to a capacitive deionization electrode and a capacitive deionization device. Background Technology
[0002] In household water use, the mainstream solutions for filtering out charged ions in water currently include ultrafiltration, nanofiltration, and reverse osmosis. Among them, reverse osmosis technology has become the market choice due to its excellent filtration effect (99%). However, this also brings a problem: with people's increasing awareness of drinking water and their focus on health, reverse osmosis water is too pure and does not retain beneficial mineral ions. Therefore, capacitive deionization technology, which retains ions, is receiving increasing research attention in water purification scenarios. Capacitive deionization technology can achieve different water qualities under different voltages, while retaining beneficial ions and removing heavy metal ions. However, its relatively short lifespan currently limits its further application in water purification. Summary of the Invention
[0003] The present invention aims to at least partially solve one of the technical problems in the prior art. Therefore, one object of the present invention is to provide a capacitive deionization electrode and a capacitive deionization device.
[0004] In a first aspect, the present invention provides a capacitive deionization electrode. According to an embodiment of the present invention, the capacitive deionization electrode includes a current collector and an active material layer, the active material layer being adjacent to at least one side of the current collector, the active material layer comprising activated carbon, resin, a conductive agent, and a binder, the electrode being a positive electrode, the resin in the active material layer being an anion exchange resin, and the electrode being a negative electrode, the resin in the active material layer being a cation exchange resin, the mass ratio of activated carbon to the resin being (1~2):(3~1).
[0005] According to the capacitive deionization electrode of the present invention, the active material layer includes activated carbon, resin, conductive agent, and binder. By doping the activated carbon with resin, the resin has a network structure. On the one hand, it can form special resin "channels," thereby accelerating the transfer and adsorption of ions. On the other hand, the network structure of the resin can maintain the pore structure of the activated carbon, preventing the collapse of the activated carbon adsorption pores, improving the adsorption performance of the activated carbon and extending its effective life, thereby improving the ion removal performance and cycle life of the electrode. In addition, the resin contains a large number of active groups such as sulfonic acid groups and amino groups. These groups can adsorb anions and cations in the solution, thereby improving the adsorption performance of the electrode. At the same time, the preferential adsorption of ions by the exchange groups of the resin reduces the common ion effect of the activated carbon, thereby extending the electrode life. In particular, the inventors have found that the mass ratio of activated carbon to resin needs to be controlled within the range of (1~2):(3~1). That is, if too little resin is added, the shielding effect of the common ion effect of the active groups in the resin cannot be effectively exerted; if too much resin is added, it will affect the intrinsic adsorption of the activated carbon, causing a decrease in performance. Therefore, the electrode has a high ion removal rate and a long cycle life.
[0006] In addition, the capacitive deionization electrode according to the above embodiments of the present invention also has the following technical features: In some embodiments of the present invention, the resin has a particle size of 2µm to 100µm, preferably 5µm to 15µm. This improves the ion removal rate and cycle life of the electrode.
[0007] In some embodiments of the present invention, the activated carbon has a particle size of 6 μm to 8 μm and a specific surface area of 1000 m². 2 / g~3000m 2 / g, wherein the activated carbon has a pore size of 0.1nm~10nm. This improves the ion removal rate and cycle life of the electrode.
[0008] In some embodiments of the present invention, the conductive agent accounts for 3% to 10% of the total mass of the active material layer. This improves the conductivity of the electrode.
[0009] In some embodiments of the present invention, the binder accounts for 5% to 10% of the total mass of the active material layer. This improves the contactability of the electrode raw materials.
[0010] In some embodiments of the present invention, the anion exchange resin includes at least one of IRA402 anion exchange resin, IRA900 anion exchange resin, and type 717 anion exchange resin.
[0011] In some embodiments of the present invention, the cation exchange resin includes at least one of SR1LNa cation exchange resin, IR120 cation exchange resin, 732 cation exchange resin, and HP1110 cation exchange resin.
[0012] In some embodiments of the present invention, the thickness of the active material layer is 60 μm to 95 μm. This improves the ion removal rate and cycle life of the electrode.
[0013] In some embodiments of the present invention, the active material layer comprises a stacked first active material layer and a second active material layer, the first active material layer being adjacent to the current collector, the first active material layer comprising activated carbon, a conductive agent, and a binder, and the second active material layer comprising activated carbon, a resin, a conductive agent, and a binder. This improves the ion removal rate and cycle life of the electrode.
[0014] In some embodiments of the present invention, the thickness of the first active material layer is 60um to 95um, and the total thickness of the first active material layer and the second active material layer is not greater than 150um.
[0015] In some embodiments of the present invention, the active material layer comprises a stacked third active material layer and a fourth active material layer, the third active material layer being adjacent to the current collector, the third active material layer comprising activated carbon, a conductive agent, and a binder, and the fourth active material layer comprising activated carbon, a binder, and a resin. This improves the ion removal rate and cycle life of the electrode.
[0016] In some embodiments of the present invention, the thickness of the third active material layer is 60um to 95um, and the total thickness of the third active material layer and the fourth active material layer is not greater than 150um.
[0017] In some embodiments of the present invention, the active material layer comprises a stacked fifth active material layer and a sixth active material layer, the fifth active material layer being adjacent to the current collector, the fifth active material layer comprising activated carbon, a conductive agent, and a binder, and the sixth active material layer comprising a conductive agent, a binder, and a resin. This can improve the ion removal rate and cycle life of the electrode.
[0018] In some embodiments of the present invention, the thickness of the fifth active material layer is 60um to 95um, and the total thickness of the fifth active material layer and the sixth active material layer is not greater than 150um.
[0019] In a second aspect, the present invention provides a capacitive deionization device. According to an embodiment of the present invention, the capacitive deionization device includes the aforementioned capacitive deionization electrode. Therefore, the capacitive deionization device has a high ion removal rate and a long service life. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0021] Figure 1 This is a schematic diagram of a capacitor deionization electrode structure according to an embodiment of the present invention; Figure 2 This is a schematic diagram of the capacitive deionization electrode structure according to another embodiment of the present invention. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0023] The lifespan of capacitive deionization electrodes decreases during long-term cycling mainly due to two factors. Firstly, during normal adsorption, the activated carbon on the electrode is easily oxidized, causing the adsorption pores of the activated carbon to collapse and performance to decline. Secondly, during the reverse electrode test, some ions cannot be completely removed due to the common ion effect, and the pores become blocked, preventing further ion adsorption.
[0024] In view of this, in a first aspect, the present invention provides a capacitive deionization electrode. According to an embodiment of the present invention, reference is made to... Figure 1 The capacitive deionization electrode includes a current collector 100 and an active material layer 200. The active material layer 200 is adjacent to at least one side of the current collector 100. The active material layer 200 includes activated carbon, resin, conductive agent and binder. The electrode is a positive electrode. The resin in the active material layer 200 is an anion exchange resin. The electrode is a negative electrode. The resin in the active material layer 200 is a cation exchange resin. The mass ratio of activated carbon to resin is (1~2):(3~1).
[0025] According to the capacitive deionization electrode of the above embodiments of the present invention, the active material layer 200 includes activated carbon, resin, conductive agent, and binder. By doping the activated carbon with resin, the resin has a network structure. On the one hand, it can form special resin "channels," thereby accelerating the transfer and adsorption of ions. On the other hand, the network structure of the resin can maintain the pore structure of the activated carbon, preventing the collapse of the activated carbon adsorption pores, improving the adsorption performance of the activated carbon and extending its effective life, thereby improving the ion removal performance and cycle life of the electrode. In addition, the resin contains a large number of active groups such as sulfonic acid groups and amino groups. These groups can adsorb anions and cations in the solution, thereby improving the adsorption performance of the electrode. At the same time, the preferential adsorption of ions by the exchange groups of the resin reduces the common ion effect of the activated carbon, thereby extending the electrode life. In particular, the inventors have found that the mass ratio of activated carbon to resin needs to be controlled within the range of (1~2):(3~1). That is, if too little resin is added, the shielding effect of the active groups in the resin on the common ion effect cannot be effectively exerted; if too much resin is added, it will affect the intrinsic adsorption of the activated carbon, causing a decline in performance. For example, the mass ratio of activated carbon to resin can be 1:3, 1:2, 1:1.5, 1:1, 2:1.5, 2:1, etc. Other examples include mass ratios greater than or equal to 1:3, 1:2, and 1, and less than or equal to 2, such as 2:1.5 and 1. Therefore, this electrode exhibits a high ion removal rate and a long cycle life.
[0026] It should be noted that the current collector, conductive agent, and binder are conventional materials in the art, and those skilled in the art can select them according to actual needs. For example, the current collector includes, but is not limited to, copper foil, aluminum foil, stainless steel foil, titanium foil, nickel foil, etc. The conductive agent includes, but is not limited to, acetylene black, conductive carbon black, graphite powder, etc. The binder includes, but is not limited to, polyurethane, polystyrene, polyacrylate, polytetrafluoroethylene, etc.
[0027] According to embodiments of the present invention, the particle size of the resin is 2µm to 100µm, preferably 5µm to 15µm. For example, the resin particle size is 2µm, 5µm, 10µm, 15µm, 20µm, 30µm, 40µm, 50µm, 60µm, 70µm, 80µm, 90µm, 100µm, etc.; and particle sizes greater than or equal to 2µm, 5µm, 10µm, 15µm, 20µm, 30µm, etc., and less than or equal to 40µm, 50µm, 60µm, 70µm, 80µm, 90µm, 100µm, etc. The inventors have discovered that controlling the resin particle size within the range of 2µm to 100µm can, on the one hand, maintain the resin's network structure and the loaded active groups, leveraging its structural advantages to accelerate ion transport and capture corresponding ions; on the other hand, during production and processing, phenomena such as detachment, cracking, and peeling will not occur due to excessively large or small particle sizes.
[0028] According to an embodiment of the present invention, the activated carbon has a particle size of 6 μm to 8 μm and a specific surface area of 1000 m². 2 / g~3000m 2 / g, the pore size of the activated carbon is 0.1nm~10nm. For example, the particle size of the activated carbon is 6um, 6.5um, 7um, 7.5um, 8um, etc., or the particle size is greater than or equal to 6um, 6.5um, 7um, etc., and less than or equal to 7.5um, 8um, etc.; for example, the specific surface area of the activated carbon is 1000m². 2 / g, 1500m 2 / g, 2000m 2 / g, 1500m 2 / g, 3000m 2 / g, etc., and for example, a specific surface area greater than or equal to 1000m² 2 / g, 1500m 2 / g, 2000m 2 / g, etc., less than or equal to 1500m 2 / g, 3000m 2 / g, etc. For example, the pore size of activated carbon is 0.1nm, 1nm, 2nm, 3nm, 4nm, 6nm, 7nm, 8nm, 9nm, 10nm, etc., and further, the pore size is greater than or equal to 0.1nm, 1nm, 2nm, 3nm, 4nm, etc., and less than or equal to 6nm, 7nm, 8nm, 9nm, 10nm, etc. The inventors found that during the adsorption process, the larger the specific surface area of activated carbon, the more adsorption active sites it can provide, and the greater the adsorption capacity. There is a close relationship between specific surface area and pore size distribution; the smaller the pore size, the larger the specific surface area of the adsorbent. Considering the application scenario of adsorbing ions in water (most ions are smaller than 1nm), the pore size is preferably in the range of 0.1nm to 10nm. Considering the uniformity of the slurry, the particle size is preferably in the range of 6um to 8um.
[0029] According to embodiments of the present invention, the mass percentage of the conductive agent is 3% to 10% based on the total mass of the active material layer. For example, the mass percentage can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., or greater than or equal to 3%, 4%, 5%, 6%, etc., and less than or equal to 7%, 8%, 9%, 10%, etc. By controlling the mass percentage of the conductive agent within the range of 3% to 10%, the conductivity of the electrode can be improved.
[0030] According to embodiments of the present invention, the mass percentage of the binder is 5% to 10% based on the total mass of the active material layer. For example, the mass percentage can be 5%, 6%, 7%, 8%, 9%, 10%, etc., or greater than or equal to 5%, 6%, etc., and less than or equal to 7%, 8%, 9%, 10%, etc. By controlling the mass percentage of the binder within the range of 5% to 10%, the contactability of the electrode raw materials can be improved.
[0031] According to embodiments of the present invention, the anion exchange resin includes, but is not limited to, IRA402 anion exchange resin, IRA900 anion exchange resin, and 717 type anion exchange resin.
[0032] According to embodiments of the present invention, the cation exchange resin includes, but is not limited to, SR1LNa cation exchange resin, IR120 cation exchange resin, 732 cation exchange resin, HP1110 cation exchange resin, etc.
[0033] According to embodiments of the present invention, the thickness of the active material layer is 60 μm to 95 μm. For example, thicknesses of 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, and 95 μm are possible; further examples include thicknesses greater than or equal to 60 μm, 65 μm, 70 μm, and 75 μm, and less than or equal to 80 μm, 85 μm, 90 μm, and 95 μm. The inventors have found that when the thickness of the active material layer is controlled within the range of 60 μm to 95 μm, the electrode exhibits excellent adsorption performance and effectively prevents electrode cracking.
[0034] According to an embodiment of the present invention, reference Figure 2 The active material layer 200 comprises a first active material layer 210 and a second active material layer 220 stacked together. The first active material layer 210 is adjacent to the current collector 100. The first active material layer 210 comprises activated carbon, a conductive agent, and a binder. The second active material layer 220 comprises activated carbon, resin, a conductive agent, and a binder. The inventors have discovered that in this dual-layer structure, the second active material layer 220 captures ions and shields against like ions, while the first active material layer 210 adsorbs and stores the captured ions, thus synergistically increasing the overall adsorption capacity. Furthermore, due to the protective effect of the second active material layer 220, the activated carbon in the first active material layer 210 is less susceptible to oxidation and pore collapse, thereby extending the overall electrode lifespan.
[0035] According to an embodiment of the present invention, the thickness of the first active material layer 210 is 60um to 95um, such as greater than or equal to 60um, 65um, 70um, 75um, etc., and less than or equal to 80um, 85um, 90um, 95um, etc., and the total thickness of the first active material layer 210 and the second active material layer 220 is not greater than 150um.
[0036] According to an embodiment of the present invention, based on the total mass of the active material layer 200, the mass percentage of the conductive agent is 3% to 10%, and the mass percentage of the binder is 5% to 15%. For example, the mass percentage of the conductive agent is greater than or equal to 3%, 4%, 5%, etc., and less than or equal to 6%, 8%, 10%, etc.; the mass percentage of the binder is greater than or equal to 5%, 6%, 7%, etc., and less than or equal to 8%, 10%, 12%, 15%, etc.
[0037] According to an embodiment of the present invention, the active material layer comprises a stacked third active material layer and a fourth active material layer, the third active material layer being adjacent to the current collector, the third active material layer comprising activated carbon, a conductive agent, and a binder, and the fourth active material layer comprising activated carbon, a binder, and a resin. This improves the ion removal rate and cycle life of the electrode.
[0038] According to an embodiment of the present invention, the thickness of the third active material layer is 60um to 95um. For example, the thickness is greater than or equal to 60um, 65um, 70um, 75um, etc., and less than or equal to 80um, 85um, 90um, 95um, etc., and the total thickness of the third active material layer and the fourth active material layer is not greater than 150um.
[0039] According to an embodiment of the present invention, based on the total mass of the third active material layer, the conductive agent accounts for 3% to 10% of the mass, and the binder accounts for 5% to 15% of the mass. For example, the mass percentage of the conductive agent is greater than or equal to 3%, 4%, 5%, etc., and less than or equal to 6%, 8%, 10%, etc.; the mass percentage of the binder is greater than or equal to 5%, 6%, 7%, etc., and less than or equal to 8%, 10%, 12%, 15%, etc.
[0040] According to an embodiment of the present invention, the mass percentage of the adhesive is 10% to 15% based on the total mass of the fourth active material layer. For example, the mass percentage is greater than or equal to 10%, 11%, 12%, etc., and less than or equal to 13%, 14%, 15%, etc.
[0041] According to an embodiment of the present invention, based on the total mass of the fourth active material layer, the mass ratio of the activated carbon to the resin is 1:(1~20). For example, the mass ratio is greater than or equal to 1:20, 1:18, 1:15, 1:10, etc., and less than or equal to 1:8, 1:5, 1:3, 1:1, etc.
[0042] According to an embodiment of the present invention, the active material layer comprises a fifth active material layer and a sixth active material layer stacked together, the fifth active material layer being adjacent to the current collector, the fifth active material layer comprising activated carbon, a conductive agent, and a binder, and the sixth active material layer comprising a conductive agent, a binder, and a resin. This improves the ion removal rate and cycle life of the electrode.
[0043] According to an embodiment of the present invention, the thickness of the fifth active material layer is 60um to 95um. For example, the thickness is greater than or equal to 60um, 65um, 70um, 75um, etc., and less than or equal to 80um, 85um, 90um, 95um, etc., and the total thickness of the fifth active material layer and the sixth active material layer is not greater than 150um.
[0044] According to an embodiment of the present invention, the mass percentage of the adhesive is 10% to 15% based on the total mass of the sixth active material layer. For example, the mass percentage is greater than or equal to 10%, 11%, 12%, etc., and less than or equal to 13%, 14%, 15%, etc.
[0045] According to an embodiment of the present invention, based on the total mass of the sixth active material layer, the mass percentage of the conductive agent is 10% to 45%. For example, the mass percentage is greater than or equal to 10%, 15%, 20%, etc., and less than or equal to 45%, 40%, 30%, etc.
[0046] According to an embodiment of the present invention, a method for preparing the above-mentioned capacitor deionization electrode includes: mixing activated carbon, resin, conductive agent, and binder in a solvent, applying the mixture to at least one side of a current collector, and drying and rolling the mixture to obtain the capacitor deionization electrode. The solvent includes, but is not limited to, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0047] According to an embodiment of the present invention, another method for preparing the above-mentioned capacitor deionization electrode includes: mixing activated carbon, a conductive agent, and a binder in a first solvent and applying the mixture to at least one side of a current collector, followed by drying and rolling to obtain a first active material layer; mixing activated carbon, a resin, a conductive agent, and a binder in a second solvent and applying the mixture to the side of the first active material layer away from the current collector, followed by drying and rolling to obtain a titanium dioxide mixed carbon capacitor deionization electrode. The first solvent includes, but is not limited to, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide, and the second solvent includes, but is not limited to, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0048] According to an embodiment of the present invention, another method for preparing the above-mentioned capacitor deionization electrode includes: mixing activated carbon, a conductive agent, and a binder in a third solvent and applying the mixture to at least one side of a current collector, followed by drying and rolling to obtain a third active material layer; mixing activated carbon, a resin, and a binder in a fourth solvent and applying the mixture to the side of the third active material layer away from the current collector, followed by drying and rolling to obtain a titanium dioxide mixed carbon capacitor deionization electrode. The third solvent includes, but is not limited to, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide, and the fourth solvent includes, but is not limited to, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0049] According to an embodiment of the present invention, another method for preparing the above-mentioned capacitor deionization electrode includes: mixing activated carbon, a conductive agent, and a binder in a fifth solvent and applying the mixture to at least one side of a current collector, followed by drying and rolling to obtain a fifth active material layer; mixing a conductive agent, a resin, and a binder in a sixth solvent and applying the mixture to the side of the fifth active material layer away from the current collector, followed by drying and rolling to obtain a titanium dioxide mixed carbon capacitor deionization electrode. The fifth solvent includes, but is not limited to, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide, and the sixth solvent includes, but is not limited to, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0050] In a second aspect, the present invention provides a capacitive deionization device. According to an embodiment of the present invention, the capacitive deionization device includes the aforementioned capacitive deionization electrode. Therefore, the capacitive deionization device has a high ion removal rate and a long service life. It should be noted that the features and advantages described above for the capacitive deionization electrode also apply to the capacitive deionization device, and will not be repeated here.
[0051] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field, or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased through legitimate channels.
[0052] Preparation of negative electrode A: The resin (SR1LNa cation exchange resin) particles were ground into powder of about 15 μm, and activated carbon (activated carbon particle size of 7 μm, specific surface area of 1900 m²) was prepared. 2 / g (pore size 3nm): The corresponding mass of conductive carbon black: binder: resin = 60:4:6:30 is weighed and mixed into powder. After mixing, the solid powder is added to the solvent N-methylpyrrolidone to form a 30% solid content solution. After stirring with a mixer for 4 hours, a uniform slurry is formed. Then, it is coated onto the current collector using a scraping device, dried at 80℃ for 4 hours, and rolled with a 90T roller press to form a resin modified electrode with a coating thickness of 85um.
[0053] Preparation of negative electrode B: The resin (SR1LNa cation exchange resin) particles were ground into powder of about 15 μm. The appropriate mass of activated carbon: conductive carbon black: binder: resin = 45:4:6:45 was weighed and mixed. After mixing, the solid powder was added to the solvent N-methylpyrrolidone to form a 30% solid content solution. The solution was stirred for 4 hours to form a uniform slurry. The slurry was then coated onto the current collector using a scraping device and dried at 80℃ for 4 hours. After rolling with a 90T roller press, a resin-modified electrode with a coating thickness of 85 μm was formed.
[0054] Preparation of negative electrode C: The resin (SR1LNa cation exchange resin) particles were ground into powder of about 15 μm. The corresponding mass of activated carbon: conductive carbon black: binder: resin = 30:4:6:60 was weighed and mixed. After mixing, the solid powder was added to the solvent N-methylpyrrolidone to form a 30% solid content solution. The solution was stirred for 4 hours to form a uniform slurry. The slurry was then coated onto the current collector using a scraping device and dried at 80℃ for 4 hours. After rolling with a 90T roller press, a resin-modified electrode with a coating thickness of 85 μm was formed.
[0055] Preparation of negative electrode D: The resin (SR1LNa cation exchange resin) particles were ground into powder of about 50 μm. The corresponding mass of activated carbon: conductive carbon black: binder: resin = 45:4:6:45 was weighed and mixed. After mixing, the solid powder was added to the solvent N-methylpyrrolidone to form a 30% solid content solution. The solution was stirred for 4 hours to form a uniform slurry. The slurry was then coated onto the current collector using a scraping device and dried at 80℃ for 4 hours. After rolling with a 90T roller press, a resin-modified electrode with a coating thickness of 85 μm was formed.
[0056] Preparation of negative electrode E: The resin (SR1LNa cation exchange resin) particles were ground into powder of about 100 μm. The corresponding mass of activated carbon: conductive carbon black: binder: resin = 45:4:6:45 was weighed and mixed. After mixing, the solid powder was added to the solvent N-methylpyrrolidone to form a 30% solid content solution. The mixture was stirred for 4 hours to form a uniform slurry. The slurry was then coated onto the current collector using a scraping device and dried at 80℃ for 4 hours. After rolling with a 90T roller press, a resin-modified electrode with a coating thickness of 85 μm was formed.
[0057] Preparation of negative electrode F (double-layer structure): The resin (SR1LNa cation exchange resin) particles were ground into powder of about 15 μm. The corresponding mass of activated carbon: conductive carbon black: binder: resin = 30:4:6:60 was weighed. The mass of each powder weighed was the same as the mass of powder weighed for preparing the negative electrode. First, 50 wt% of activated carbon, conductive carbon black and binder were mixed. After mixing, the solid powder was added to the solvent N-methylpyrrolidone to form a 30% solid content mixed solution. After stirring with a stirrer for 4 hours, a uniform slurry was formed. Then, it was coated onto the current collector with a scraping device and dried at 80℃ for 4 hours. After rolling with a 90T roller press, a first active material layer with a thickness of 85 μm was formed on the current collector. Then, the remaining 50wt% of activated carbon, conductive carbon black, binder and resin are mixed. After mixing, the solid powder is added to the solvent N-methylpyrrolidone to form a 30% solid content mixed solution. After stirring with a mixer for 4 hours, a uniform slurry is formed. Then, it is coated onto the current collector using a scraping device and dried at 80℃ for 4 hours. After rolling with a 60T roller press, a second active material layer with a thickness of 50µm is formed on the first active material layer, thereby preparing a double-layer electrode.
[0058] Preparation of negative electrode G (double-layer structure): The resin (SR1LNa cation exchange resin) particles were ground into powder of about 15 μm. The corresponding mass of activated carbon: conductive carbon black: binder = 60:5:7 was weighed and mixed. After mixing, the solid powder was added to the solvent to form a 30% solid content solution. The solution was stirred for 4 hours to form a uniform slurry. The slurry was then coated onto the current collector using a scraping device and dried at 80℃ for 4 hours. After rolling with a 90T roller press, an electrode with a coating thickness of 85 μm was formed. Subsequently, the powder of activated carbon: resin: binder = 44:44:12 was weighed and mixed to form a 30% solid content slurry. The slurry was coated onto the previously prepared coating and dried at 80℃ for 4 hours. After rolling with a 60T roller press, a double-layer structure electrode with a total coating thickness of 120 μm was formed.
[0059] Preparation of negative electrode H (double-layer structure): The resin (SR1LNa cation exchange resin) particles were ground into powder of about 15 μm. The corresponding mass of activated carbon: conductive carbon black: binder = 60:5:7 was weighed and mixed. After mixing, the solid powder was added to the solvent to form a 30% solid content solution. The solution was stirred for 4 hours to form a uniform slurry. The slurry was then coated onto the current collector using a scraping device. After drying at 80℃ for 4 hours, it was rolled using a 90T roller press to form an electrode with a coating thickness of 85 μm. Subsequently, the mass of conductive carbon black: resin: binder = 44:44:12 was weighed to form a 30% solid content slurry. The slurry was applied to the electrode prepared above to form a new coating. After drying at 80℃ for 4 hours, it was rolled using a 60T roller press to form a resin-coated electrode with a total coating thickness of 120 μm.
[0060] Preparation of negative electrode X: The resin (SR1LNa cation exchange resin) particles were ground into powder of about 15 μm. The corresponding mass of activated carbon: conductive carbon black: binder: resin = 65:4:6:25 was weighed and mixed. After mixing, the solid powder was added to the solvent N-methylpyrrolidone to form a 30% solid content solution. The solution was stirred for 4 hours to form a uniform slurry. The slurry was then coated onto the current collector using a scraping device and dried at 80℃ for 4 hours. After rolling with a 90T roller press, a resin-modified electrode with a coating thickness of 85 μm was formed.
[0061] Preparation of negative electrode Y: The resin (SR1LNa cation exchange resin) particles were ground into powder of about 15 μm. The corresponding mass of activated carbon: conductive carbon black: binder: resin = 20:4:6:70 was weighed and mixed. After mixing, the solid powder was added to the solvent N-methylpyrrolidone to form a 30% solid content solution. The solution was stirred for 4 hours to form a uniform slurry. The slurry was then coated onto the current collector using a scraping device and dried at 80℃ for 4 hours. After rolling with a 90T roller press, a resin-modified electrode with a coating thickness of 85 μm was formed.
[0062] Preparation of positive electrode A: The difference between positive electrode A and negative electrode A is that the resin used for positive electrode A is IRA402 anion exchange resin.
[0063] Preparation of positive electrode B: The difference between positive electrode B and negative electrode B is that the resin used for positive electrode B is IRA402 anion exchange resin.
[0064] Preparation of positive electrode C: The difference between positive electrode C and negative electrode C is that the resin used for positive electrode C is IRA402 anion exchange resin.
[0065] Preparation of positive electrode D: The difference between positive electrode D and negative electrode D is that the resin used for positive electrode D is IRA402 anion exchange resin.
[0066] Preparation of positive electrode E: The difference between positive electrode E and negative electrode E is that the resin used for positive electrode E is IRA402 anion exchange resin.
[0067] Preparation of positive electrode F (double-layer structure): The difference between positive electrode F and negative electrode F is that the resin used for positive electrode F is IRA402 anion exchange resin.
[0068] Preparation of positive electrode G (double-layer structure): The difference between positive electrode G and negative electrode G is that the resin used for positive electrode G is IRA402 anion exchange resin.
[0069] Preparation of positive electrode H (double-layer structure): The difference between positive electrode H and negative electrode H is that the resin used for positive electrode H is IRA402 anion exchange resin.
[0070] Preparation of positive electrode X: The difference between positive electrode X and negative electrode X is that the resin used for positive electrode X is IRA402 anion exchange resin.
[0071] Preparation of positive electrode Y: The difference between positive electrode Y and negative electrode Y is that the resin used for positive electrode Y is IRA402 anion exchange resin.
[0072] Conventional positive / negative electrode: Weigh the appropriate mass of activated carbon: conductive carbon black: binder in a weight ratio of 88:5:7 and mix the powders. After mixing, add the solid powder to the solvent to form a 30% solid content solution. Stir for 4 hours to form a uniform slurry. Then, use a scraping device to scrape it onto the current collector. Dry at 80℃ for 4 hours. After rolling with a 90T roller press, a positive / negative electrode with a coating thickness of 85um is formed.
[0073] Capacitor deionization devices are prepared using the different positive and negative electrodes mentioned above: a spiral-wound capacitor deionization device is prepared by alternating positive electrode-mesh-negative electrode-mesh arrangement.
[0074] The performance of the devices prepared in the examples and comparative examples was tested, as follows: Ion removal rate (calcium ion, magnesium ion, sodium ion, potassium ion, carbonate ion, sulfate ion, bicarbonate ion, chloride ion): Record the initial ion content T1 and the ion content T2 after flowing through the capacitor deionization module. Then the ion removal rate = (1-T2 / T1)*100%.
[0075] Number of cycles: The number of cycles is the number of cycles when the ion removal rate is 50% of the ion removal rate of the first cycle (positive voltage 1.6V, 150s, negative voltage 1.6V, 100s is the voltage and time applied in one cycle).
[0076] Table 1 shows the types of electrodes used in the examples and comparative examples, as well as the device performance test results.
[0077] Table 1
[0078] As shown in Table 1, the devices fabricated using the electrodes of this application not only exhibit excellent ion removal rates but also long cycle life. Furthermore, devices with a double-layer active material layer perform better than those with a single-layer active material layer. The optimal coating method for the second layer in the double-layer structure is resin, conductive agent, and binder.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A capacitive deionization electrode, characterized in that, The capacitive deionization electrode includes a current collector and an active material layer. The active material layer is a single-layer structure and is adjacent to at least one side of the current collector. The active material layer includes activated carbon, resin, a conductive agent, and a binder. The mass ratio of activated carbon to resin in the active material layer is (1~2):(3~1). Based on the total mass of the active material layer, the mass percentage of the conductive agent is 3%~10%. The specific surface area of the activated carbon is 1000 m². 2 / g~3000m 2 / g, wherein the pore size of the activated carbon is 0.1nm~10nm; when the electrode is a positive electrode, the resin in the active material layer is an anion exchange resin, and when the electrode is a negative electrode, the resin in the active material layer is a cation exchange resin.
2. The capacitive deionization electrode according to claim 1, characterized in that, The resin has a particle size of 2μm to 100μm.
3. The capacitive deionization electrode according to claim 2, characterized in that, The resin has a particle size of 5μm to 15μm.
4. The capacitive deionization electrode according to claim 1, characterized in that, The activated carbon has a particle size of 6μm to 8μm.
5. The capacitive deionization electrode according to any one of claims 1-4, characterized in that, The adhesive accounts for 5% to 10% of the total mass of the active material layer.
6. The capacitive deionization electrode according to any one of claims 1-4, characterized in that, The anion exchange resin includes at least one of IRA402 anion exchange resin, IRA900 anion exchange resin, and 717 type anion exchange resin; And / or, the cation exchange resin includes at least one of SR1LNa cation exchange resin, IR120 cation exchange resin, 732 cation exchange resin, and HP1110 cation exchange resin.
7. The capacitive deionization electrode according to any one of claims 1-4, characterized in that, The thickness of the active material layer is 60μm~95μm.
8. A capacitive deionization electrode, characterized in that, The capacitive deionization electrode includes a current collector and an active material layer. The active material layer has a double-layer structure, consisting of a first active material layer and a second active material layer stacked together. The first active material layer is adjacent to the current collector. The first active material layer includes activated carbon, a conductive agent, and a binder. The second active material layer includes activated carbon, resin, a conductive agent, and a binder. The mass ratio of activated carbon to resin in the second active material layer is (1~2):(3~1). Based on the total mass of the active material layer, the mass percentage of the conductive agent is 3%~10%. The specific surface area of the activated carbon is 1000 m². 2 / g~3000m 2 / g, wherein the pore size of the activated carbon is 0.1nm~10nm; When the electrode is a positive electrode, the resin in the active material layer is an anion exchange resin; when the electrode is a negative electrode, the resin in the active material layer is a cation exchange resin. And / or, the thickness of the first active material layer is 60μm~95μm, and the total thickness of the first active material layer and the second active material layer is not greater than 150μm.
9. The capacitive deionization electrode according to claim 8, characterized in that, The resin has a particle size of 2μm to 100μm.
10. The capacitive deionization electrode according to claim 9, characterized in that, The resin has a particle size of 5μm to 15μm.
11. The capacitive deionization electrode according to claim 8, characterized in that, The activated carbon has a particle size of 6μm to 8μm.
12. A capacitive deionization electrode, characterized in that, The capacitive deionization electrode includes a current collector and an active material layer. The active material layer has a double-layer structure, consisting of a stacked third active material layer and a fourth active material layer. The third active material layer is adjacent to the current collector and includes activated carbon, a conductive agent, and a binder. The fourth active material layer includes activated carbon, a binder, and a resin. The mass ratio of activated carbon to resin in the fourth active material layer is (1~2):(3~1). Based on the total mass of the third active material layer, the mass percentage of the conductive agent is 3%~10%. The specific surface area of the activated carbon is 1000 m². 2 / g~3000m 2 / g, wherein the pore size of the activated carbon is 0.1nm~10nm; When the electrode is a positive electrode, the resin is an anion exchange resin; when the electrode is a negative electrode, the resin is a cation exchange resin. And / or, the thickness of the third active material layer is 60μm~95μm, and the total thickness of the third active material layer and the fourth active material layer is not greater than 150μm.
13. The capacitive deionization electrode according to claim 12, characterized in that, The resin has a particle size of 2μm to 100μm.
14. The capacitive deionization electrode according to claim 13, characterized in that, The resin has a particle size of 5μm to 15μm.
15. The capacitive deionization electrode according to claim 12, characterized in that, The activated carbon has a particle size of 6μm to 8μm.
16. A capacitive deionization electrode, characterized in that, Resin particles were ground into 15μm powder. The appropriate weights of activated carbon, conductive carbon black, and binder were weighed and mixed in a ratio of 60:5:
7. The mixed powder was then added to a solvent to form a 30% solids solution. The solution was stirred for 4 hours to form a uniform slurry, which was then coated onto a current collector using a scraping device. After drying at 80℃ for 4 hours, the slurry was rolled using a 90T roller press to form an electrode with a coating thickness of 85μm. Subsequently, conductive carbon black, resin, and binder were weighed in a ratio of 44:44:12 to form a 30% solids slurry. This slurry was applied to the previously prepared electrode to form a new coating. After drying at 80℃ for 4 hours, the slurry was rolled using a 60T roller press to form a resin-coated electrode with a total coating thickness of 120μm. The specific surface area of the activated carbon was 1000m². 2 / g~3000m 2 / g, wherein the pore size of the activated carbon is 0.1nm~10nm; When the electrode is a positive electrode, the resin is an anion exchange resin; when the electrode is a negative electrode, the resin is a cation exchange resin.
17. The capacitive deionization electrode according to claim 16, characterized in that, The activated carbon has a particle size of 6μm to 8μm.
18. A capacitor deionization device, characterized in that, Includes the capacitive deionization electrode as described in any one of claims 1-17.
Citation Information
Patent Citations
Preparation method of ion exchange resin substrate and activated carbon integrated electrode for capacitive desalination
CN105776451A
Resin composite activated carbon double-layer electrode as well as preparation method and application thereof
CN107445253A